(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify the level of awareness of preventive exercises among students of the College of Physical Education and Sport Sciences, as well as the extent of their practice of these exercises. The study also examined the relationship between the type of sports activity practiced and the level of preventive awareness among students. The researcher adopted the descriptive survey method as it was deemed appropriate for the objectives of the study. The research population consisted of students from the College of Physical Education and Sport Sciences at Ghreiban University, totaling 162 students. A random sample of 58 students was selected, representing 35.5% of the total study population. Data were collected through reviewing relevant literature and previous studies addressing awareness and its relationship to injury prevention. In addition, a questionnaire was designed by the researcher as the primary tool for data collection in order to achieve the study objectives. Appropriate statistical methods were employed to analyze the collected data. The results of the statistical analysis indicated that students demonstrated a high level of awareness regarding the importance of preventive exercises, particularly in their role in reducing sports-related injuries. The findings also highlighted the need to encourage the implementation of preventive exercises as a regular practical component in students’ training routines, as well as the importance of integrating such exercises into the training programs and sports activities conducted within the college.